Tingkat Kerentanan Bencana Kebakaran dalam tinjauan Sosial Fisik dan Ekonomi di Lingkungan Saleppa, Kelurahan Banggae - Nur Ratika Syamsiar (Universitas Sulawesi Barat, 2022)
Abstract Article Title. Fire is a disaster based on the cause of its occurrence classified as a natural disaster (natural disaster) or non-natural disaster caused by human negligence (man - made disaster), which can occur anytime and anywhere, regardless of the time, place or anyone so it is sufficient worrying and very undesirable because it can result in material and immaterial losses as well as environmental damage, and psychological impacts for those who experience it. Majene Regency, especially in Banggae District, has experienced a significant population growth. With, the total population in 2016 was 40,646 people a population density of 1,616 people/ha (Statistic center of Majene regency). This causes an increase in housing needs and results in the development of dense settlements, causing increased activities for meeting the needs of the community in Banggae District, especially the Saleppa Neighborhood . In the period of 2020 and 2022 there have been 2 fires in the Saleppa Neighborhood Area, including the fire incident on September 14th, 2020 which scorched 8 shop houses (Ruko), and on April 4, 2022 which scorched 2 shop houses (Ruko). In fact, in the 70s and 90s there were fires that scorched dozens of houses and shop houses. In this study, quantitative descriptive data analysis was used, namely analyzing the risk of fire disasters based on regional characteristics. From the results of the analysis through the Residential Fire Disaster Vulnerability Index, it was found that the condition of the area in the Saleppa neighborhood, Banggae Village, was included in the category of high vulnerability class for the occurrence of residential fire hazards. Keywords: Disaster, Fire, Mitigation, Dense Settlements. Abstrak Kebakaran merupakan bencana yang berdasarkan penyebab kejadiannya tergolong sebagai bencana alam (natural disaster) maupun bencana non-alam yang diakibatkan oleh kelalaian manusia (man - Made disaster), yang dapat terjadi kapan saja dan dimana saja,tidak mengenal waktu, tempat atau siapapun sehingga cukup mengkhawatirkan dan sangat tidak diinginkan karena dapat mengakibatkan kerugian baik secara material maupun immaterial serta kerusakan lingkungan, dan dampak psikologis bagi pihak yang mengalaminya. Kabupaten Majene khususnya di Kecamatan Bangge mengalami perkembangan jumlah penduduk yang cukup signifikan. Dengan, jumlah penduduk pada tahun 2016 sebanyak 40.646 jiwa dengan kepadatan penduduk 1.616 Orang/ha (BPS Kab Majene). Hal ini menyebabkan peningkayan kebutuhan perumahan dan mengakibatkan berkembangnya permukiman padat sehingga menyebabkan peningkatan aktivitas bagi bagi pemenuhan kebutuhan masyarakat di Kecamatan Banggae khususnya Lingkungan Saleppa. Dalam kurun waktu tahun 2020 dan tahun 2022 telah terjadi 2 kebakaran di Wilayah Lingkungan Saleppa antara lain kejadian kebakaran pada tanggal 14 September 2020 yang menghanguskan 8 rumah toko (Ruko), dan pada tanggal 4 April 2022 yang menghanguskan 2rumah toko (Ruko). Bahkan, di tahun 70-an dan di tahun 90-an pernah terjadi kebakaran yang menghanguskan puluhan rumah dan Ruko. Pada Studi ini digunakan analisis data deskriptif kuantitatif, yaitu menganalisa risiko bencana kebakaran berdasarkan karakteristik wilayah. Dari hasil analisis melalui Indeks Kerentanan Bencana Kebakaran Permukiman ditemukan bahwa kondisi wilayah di Lingkungan Saleppa Kelurahan Banggae, masuk dalam kategor kelas kerentanan tinggi terjadinya bahaya kebakaran permukiman. Kata Kunci: Bencana, Kebakaran, Mitigasi, Permukiman padat.